Pertanggung Jawaban Hukum oleh Seorang Dokter yang Melakukan Tindak Pidana Pemalsuan Surat Keterangan Dokter - Juli Shara Pasaribu; Chistofe Daeli; Koko Valensio Situmeang; Sonya Airini Batubara (Mahesa Research Center, 2020)
The research objectives used were to determine the ethical and legal accountability of a doctor who commits a criminal act of doctor's certificate forgery and to find out how to legally handle a criminal act committed by a doctor in the field of health law. The research method uses normative juridical, namely using library research and the source of legal materials used is secondary data. This research uses the theory of responsibility. Letter forgery issues a right which is used as false information about the presence or absence of disease. Criminal acts that often occur are related to Article 263 of the Criminal Code (making forged letters or falsifying letters) Article 266 of the Criminal Code for a doctor who falsifies a letter sentenced to a maximum imprisonment of four (4) years. A doctor is required to provide a statement and opinion that has been examined itself the truth. Overcoming letter forgery is carried out through 2 efforts, namely penal measures and non-penal measures carried out repressively (law enforcement). Prevention can be done by providing additional provisioning both ethically and in discipline to each doctor